An Appraisal Of The Supernova Minicomputer As A Process Simulation Tool - Foran, Charles (My University, 1972)
The object of this work was to evaluate the Supernova ninicomputer as a process simulation tool. To accomplish this obje c tive the GEMCS ste2dy-state simulation system wa.s programmed for the Supernova. This system was programmed to run in five different modes, BASIC , two modes which require that al.L progra1ns are written in Assembly Language, and two modes in which programs may be called from the disk. Of these latter two modes, one requires all programs to be written in Assembly Language; the other mode allows programs to be written in Assembly Language or FORTRAN IV.
Two case studies which had previously been run on the CDC 6400 were run on the Supernova to test and evaluate f our of the modes in which GEMCS was proerammed for the Supernova.
The studies have also provided an a ssessment of the hardware and softws.re facilities of the Supernova and the results of thjs assessment were documented. In addition the opera tion of the various strategies used to impl ement GEMCS have provided an indication of the feasibility of the impl ementation of the dynamic system simulation program, DYNSYS.
Keywords: supernova minicomputer, simulation tool, simulation, GEMCS stead state, supernova, Assembly Language, Basic Mode, FORTAN IV, CDC 6400, DYNSYS, dynamic system simulation program